(untitled) (Caleidoscopio. Revista de Italianistica de ADILLI, 2026)
Infinity has always been an elusive, ambiguous, and unfathomable concept. Borges considered it the corrupting element of all others. Leopardi extensively discusses the topic in his poetry and notes in the Zibaldone. However, these disturbing readings, very characteristic of Modernity, strongly contrast with medieval conceptions. So, how should we think about infinity in Dante? What exactly did the supreme poet understand, how did he conceive it? And, moreover, how to construct images of an ineffable idea? We could postulate, a priori, that in The Divine Comedy, infinity acquires multiple faces: it is a theological category to refer to divine attributes, a way of conceiving the cosmos as a whole, a moral category, and also, finally, a mathematical one. And, in a way, it implies the very essence of the poem. In this work, we will explore these multiple readings of infinity, focusing particularly on Dante’s Paradise.